2003
DOI: 10.1007/s00167-003-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical study of the meniscofibular ligament

Abstract: We examined the anatomical structure of a ligament (ligamentum meniscofibulare) between apex fibulae and lateral meniscus by macroscopic and microscopic dissection and transillumination method in 50 knees of 25 cadavers (5 were fresh). We analyzed the function of this ligament, which runs between the head of the fibulae and lateral meniscus. The existence of a connection between knee joint and proximal tibiofibular joint was demonstrated by injecting colored liquid into the knee joint space and transilluminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 20 publications
1
38
0
1
Order By: Relevance
“…However, there are no data regarding injury to this ligament and the prognosis. Bozkurt et al confirmed the presence of this ligament in all the subjects examined in their study, demonstrating increased tension of this ligament during dorsiflexion of the ankle and describing its protective function against varus forces to the knee and external rotation forces to the leg [1]. Furthermore, Bozkurt et al emphasized the need for biomechanical, radiological, and clinical studies of the meniscofibular ligament [1].…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…However, there are no data regarding injury to this ligament and the prognosis. Bozkurt et al confirmed the presence of this ligament in all the subjects examined in their study, demonstrating increased tension of this ligament during dorsiflexion of the ankle and describing its protective function against varus forces to the knee and external rotation forces to the leg [1]. Furthermore, Bozkurt et al emphasized the need for biomechanical, radiological, and clinical studies of the meniscofibular ligament [1].…”
Section: Introductionmentioning
confidence: 71%
“…Dorsiflexion of the ankle has been shown to create tension in the meniscofibular ligament. A protective function against varus and external rotation forces to the knee has been described for the meniscofibular ligament [1]. The sitting position described by the patient exactly matches the position that creates meniscofibular ligament tension (Figure 1).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations